Synthesis of Some New Phenolic Azo Schiff Bases—Part- II - Raut, A.W.; Lohakare, J.C.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
p-Toluidine on diazotisation gives p-methyl benzene diazonium chloride (I) which on condensation with salicylaldehyde gives 2-hydroxy- 5-(4-methyl phenylazo) benzaldehyde (II). This II on condensation with substituted aniline gives 2-hydroxy-5-(4-methyl phenylazo) benzylidine substituted- aniline, i.e., substituted phenolic azo Schiff bases.